Automatic Cleaning of Boiling Fluids into Pumping Stations - Musulmonov F. Sh; Ubaydullayev S.O; Namozov I.N. (Genius Journals, 2023)
According to the results of the conducted research, there is a possibility of automatic control of the discharge in front of the fences. For this, it is recommended to use potential geometric sensors of water pressure due to the accumulation of liquid in front of the grid, and it is possible to implement the technical means for the automated adjustment system, ensuring reliable operation
Keywords: Pumping stations; hydromechanical equipment; structures